KORBAN BULLYING DAN DEPRESI PADA SISWA SEKOLAH MENENGAH PERTAMA DI KOTA YOGYAKARTA - , Erni Gustina, Prof. dr. M. Hakimi, SpOG(K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Bullying is common problem in children and adolescents at school around the world. Children often bullied at school are more likely to perform bed-wetting, sleeping difficulty, headache, and abdominal pain. Anxiety, fear to go to school, feeling of being unsafe and unhappy at school, and decreased self-esteem are all consequences of repeated victims of bullying behavior. Objective: To determine the association of bullying behavior and depression in junior high school students in Yogyakarta Municipality Methods: This study an observational study, with a cross-sectional design. The study population was junior high school students in Yogyakarta Municipality. Subjects of study were as many 250 people. The sampling technique in this study was conducted with probability sampling using random sampling method. Analysis of the data was through three stages, namely univariabel analysis, bivariabel analysis using chi-square and multivariable analysis using logistic regression. Result: The bivariabel analysis showed a significant association between victim of bullying and depression (p<0,05). Multivariabel analysis between victim of bullying and depression showed a significant association (RP= 1.53